Low country : a novel - Siddons, Anne Rivers (HarperCollinsPublishers, 1998)
Caroline Venable has everything her Southern heritage promised: money, prestige, a powerful husband, and a predictable routine of country-club luncheons, cocktail parties, and dinners hosting her husband's wealthy friends, clients, and associates in his successful land-developing conglomerate. To escape her stifling routine, Caro drinks a little too much. But her true solace is the Lowcountry island her beloved Granddaddy left her, an oasis of breathtaking beauty that is home to a band of wild ponies. When Caro learns that her husband must develop the island or lose the business, she is devastated. The Lowcountry is her heritage, and what will happen to the ponies whose spirit and freedom have captivated her since childhood? Saving the island could cost Caroline more than she ever imagined. To succeed, she must confront the part of herself numbed by alcohol and careful avoidance, and shatter long-held ideals about her role in society, her marriage, and ultimately, herself.